The Metamorphosis of NAR to CRNA: The Caterpillar to Butterfly Analogy. - Glymph, Derrick C.; Rodney, Tamar; King, Daniel D.; Zhou, Rishelle Y. (AANA Journal, 2026)
The journey from nurse anesthesiology resident (NAR) to certified registered nurse anesthetist (CRNA) is a profound transformation, one that extends beyond skill acquisition to the evolution of professional identity. Using the metaphor of a caterpillar's metamorphosis into a butterfly, this article explores how academic rigor, clinical immersion, and mentorship shape resilience, adaptability, and confidence in future CRNAs. Grounded in growth mindset theory, it highlights how embracing challenges, seeking feedback, and reframing setbacks as opportunities for learning build both competence and self-efficacy. As residents transition from novice learners to autonomous practitioners, engagement with professional organizations such as the American Association of Nurse Anesthesiology becomes essential to sustaining lifelong growth and leadership. The metamorphosis from NAR to CRNA, therefore, reflects more than a change in credentials, it signifies emergence into a profession defined by reflection, excellence, and service.